Factors that can Affect Employee Work Motivation - Adam Ghaffar; Setyo Riyanto (Almana : Jurnal Manajemen dan Bisnis, 2022)
Human resources in a company organization can not be separated to achieve the organization's goal. The negative impact of work motivation has become a severe problem for a company. The negative impacts that can be felt are the lack of performance provided by the employee and reduced curiosity about the regulations that exist in the company and consider work as unimportant or the lack of incentives provided by an organization that reduces work motivation. Work motivation is expected to provide more value to carry out work properly and correctly, which aims to benefit a company organization that is being run. In this study, the number of resource persons who participated was three consisting of the Head, Leader, and Staff employees within the company. The purpose of this study is to provide an overview of the company to find out what factors affect the work motivation of employees and are expected to be implemented within the company. The method used in this research is qualitative by using interview techniques. The results show that work motivation can be increased by providing rewards or bonuses to employees so that they can motivate them to provide excellent and maximum work results.